Application of the problem based learning model and guided inquiry on learning outcomes and student interest - Anna Juniar; Debora Renita Paulina Siahaan (Jurnal Inovasi dan Teknologi Pembelajaran, 2024)
Abstrak: Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan dengan penerapan model pembelajaran berbasis masalah dan inkuiri terbimbing terhadap hasil belajar dan minat siswa. Sifat penelitian adalah eksperimen semu dengan desain kelompok kontrol pre-test dan post-test. Sampel penelitiannya adalah Kelas XI IPA 2 sebagai kelas eksperimen I dengan menggunakan model pembelajaran berbasis masalah dan Kelas XI IPA 4 sebagai kelas eksperimen II dengan menggunakan model inkuiri terbimbing. Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar dan minat siswa pada materi asam dan basa, dengan rata-rata nilai post-test Kelas Eksperimen I sebesar 88,90 dan rata-rata minat akhir sebesar 83,12; kelas adalah 83,12.Kelas II sebesar 88,90, 86,62 dan hasil akhir sebesar 82,46.Hasil temuan menunjukkan bahwa terdapat perbedaan hasil dan minat belajar siswa, serta terdapat korelasi positif antara minat dan hasil belajar pada kedua model. Kami berharap hasil penelitian ini dapat membantu para pendidik memahami dan menerapkan model pembelajaran yang inovatif dan efektif kepada siswa. Abstract: This study explores the differences between the application of problem-based learning models and guided inquiry on students’ learning outcomes and interest. This research is a pseudo-experiment with a pre-test and post-test control group design. The research sample consisted of students in the eleventh grade 2 science class who served as the experimental class I using a problem-based learning model and students in the eleventh grade 4 science class as the experimental class II using the guided inquiry model. The results showed differences in learning outcomes and student interest in acid and base materials, with an average post-test score of 88.90 and an average final interest of 83.12 from Experimental Class I. Meanwhile, the experimental class II attained an average post-test score of 88.90, 86.62 and the final result was 82.46. The findings indicated differences in student learning outcomes and interest, with a positive correlation between interest and learning outcomes in both models. It is hoped that the results of this study will assist educators in understanding and applying innovative and effective learning models to students.